The Effect of Kepok Banana (Musa balbisiana) Peel Extract on the Survival of Sangkuriang Catfish (Clarias gariepinus) Infected with Aeromonas hydrophila - Ilham Maolana; Mad Rudi; Daniel Julianto Tarigan (SiRad: Pelita Wawasan, 2025)
Bacterial infections caused by Aeromonas hydrophila are one of the main factors contributing to the failure of Sangkuriang catfish (Clarias gariepinus) aquaculture. The use of antibiotics for treatment has been prohibited due to concerns about residue accumulation and bacterial resistance, making alternative treatments necessary. One potential alternative is the utilization of kepok banana (Musa balbisiana) peel extract. This study aims to analyze the effect of administering kepok banana peel extract at different doses on the survival rate of Sangkuriang catfish infected with A. hydrophila. This research employed an experimental method using a completely randomized design (CRD) consisting of five treatments and three replications. The treatments included P0 (negative control), P1 (positive control), P2 (500 mg/L), P3 (1000 mg/L), and P4 (1500 mg/L). The catfish, measuring 7–9 cm in size, were maintained at a density of 10 fish per 10 liters, and infection was induced with A. hydrophila at a concentration of 10⁸ CFU/mL. Data analysis was conducted using ANOVA followed by Duncan’s multiple range test at a 95% confidence level (p<0.05). The results showed that the administration of kepok banana peel extract significantly affected the survival rate of Sangkuriang catfish. The highest survival rate was observed in treatment P2 (500 mg/L) with a mean value of 1.00±0.00c, which was significantly different from other treatments. Therefore, the optimal dose for enhancing the survival of A. hydrophila-infected Sangkuriang catfish is 500 mg/L.[Penyakit infeksi bakteri Aeromonas hydrophila merupakan salah satu faktor utama yang menyebabkan kegagalan dalam budidaya ikan lele sangkuriang (Clarias gariepinus). Penggunaan antibiotik sebagai penanganan telah dilarang karena efek residu dan resistensi, sehingga diperlukan alternatif pengobatan yang lebih aman, salah satunya melalui pemanfaatan ekstrak kulit pisang kepok (Musa balbisiana). Penelitian ini bertujuan untuk menganalisis pengaruh pemberian ekstrak kulit pisang kepok dengan dosis yang berbeda terhadap kelangsungan hidup ikan lele sangkuriang yang terinfeksi bakteri A. hydrophila. Penelitian ini menggunakan metode eksperimen dengan rancangan acak lengkap (RAL) yang terdiri dari lima perlakuan dan tiga kali ulangan. Perlakuan yang diberikan meliputi P0 (kontrol negatif), P1 (kontrol positif), P2 (500 mg/L), P3 (1000 mg/L), dan P4 (1500 mg/L). Ikan lele dengan ukuran 7–9 cm dipelihara dalam kepadatan 10 ekor/10 L, dan infeksi dilakukan dengan A. hydrophila pada kepadatan 10⁸ CFU/mL. Analisis data menggunakan uji ANOVA dengan uji lanjut Duncan pada taraf kepercayaan 95% (p<0,05). Hasil penelitian menunjukkan bahwa pemberian ekstrak kulit pisang kepok berpengaruh signifikan terhadap kelangsungan hidup ikan lele sangkuriang. Perlakuan P2 (500 mg/L) menghasilkan tingkat kelangsungan hidup tertinggi (1.00±0.00c), yang berbeda nyata dibandingkan perlakuan lainnya. Dengan demikian, dosis 500 mg/L merupakan dosis optimal dalam meningkatkan kelangsungan hidup ikan lele sangkuriang yang terinfeksi A. hydrophila.]